Bell : - Bruce, Robert V. (Little, Brown, 1973)
An excellent biography of the complex person who was Alexander Graham Bell. Features one chapter about his work on hydrofoils. This is reprinted on this website as Alexander Graham Bell and the Hydrofoils.